BhÃ¢jheng Nyiram, BhÃ¢jheng Ajer: Potret Pekerja Anak di Perkebunan Tembakau Madura - Latif Kusairi; Khotim Ubaidillah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
The research entitled "Bhajheng Nyiram, Bhajheng Ajer: Portrait of Child Labor in Tobacco Plantation Madua" is more using a qualitative approach as a research method. This research is also done through literature study and empirical experience in the field. The purpose of this study is to explore the portrait of child labor in Madura tobacco estates. The results of this study indicate that the cultivation of Madura tobacco is an important economic aspect for some Madurese community that has existed since the Dutch East Indies. In addition, the involvement of children in the process of tobacco cultivation in Madura is a value that has been instilled by parents early on and internalized value as to continue pengelolahan ancestral lands that will be passed on to the children of the tobacco farmers.